From Motivations to Fears: Exploration of Teachers’ Professional Identity in Yazd City - Azam Moghimi; Mehraban Parsamehr; Ali Ruhani (پژوهش‌های راهبردی مسائل اجتماعی ایران, 2023)
Introduction Profession and job are the important parts of a person's identity, indicating his/her position in the society. It is referred to as professional identity. The professional identity of teachers in Iran is facing serious challenges and we are indeed experiencing a crisis in their professional identity. In today's Iranian society, the teaching profession has become ordinary and inferior. Research documents demonstrate that the current situation has significantly decreased teachers' desire for productive work and professional affiliation. Lack of motivation, work scarcity, excessive fatigue, interest in leaving teaching profession, and feelings of regret for choosing this career have increased among teachers. Social and cultural elites have emphasized the critical importance of the professional identity of Iranian teachers. However, this issue has received less theoretical and empirical attention in Iran. Considering the problematic nature of professional identity and the existing research literature in this field, it is necessary to take a fresh look at this issue. Let's explore what teachers truly think about their identity and what they mean by their professional identity from their own perspectives. Additionally, let's examine the conditions and factors that are effective in the formation of teachers' professional identity. The professional identity of teachers is influenced by what processes it follows and how it is formed This research was conducted among teachers in Yazd City due to the educational structure of Yazd Province. It has consistently achieved the best position in the national entrance exam for the past 27 years, thus being affected by the issue of the national entrance exam. Based on the theoretical framework of this research, identity is formed during a social process and through social interactions. It is a dynamic matter that is constantly subject to change. In the approach of social identity, individuals do not simply consider different groups as the defining reference for their identity. Instead, they actively engage in this field and the ideas they have about their profession give rise to different thoughts and emotions, which in turn have varying effects on their performance. Since this research aimed to investigate the process and formation of teachers' approach to profession, Kathy Charmaz's constructivist approach was utilized. This approach places emphasis on diverse local worlds, multiple realities, and complexity of specific worlds, viewpoints, and actions. It also focuses on people's views, values, beliefs, feelings, assumptions, and ideology.